NK/T cell Lymphoma as a Rare Cause of an Oronasal Fistula - Mohd Safian, Ahmad Izani; Mohamad, Ahmad Fakrurrozi; Ramli, Ramiza Ramza; Mohamad, Irfan (Acta Medica, 2021)
NK/T cell lymphoma is one of the most unique and rare forms of extranodal non-Hodgkin’s lymphoma, mostly derived from natural killer cell lineages and occasionally cytotoxic T cell lines. Due to the non-specific presentation of NK/T cell lymphoma such as nasal obstruction, nasal discharge, and epistaxis, diagnosis is often an issue and can be misleading. Oronasal fistula following a non-healing ulcer on the soft palate, can be one of the clinical presentations of NK/T cell lymphoma. Here, we are reporting a rare case of NK/T cell lymphoma in a 32-year-old gentleman who presented with an oronasal fistula post tissue biopsy for a non-healing ulcer over the soft palate. The tissue biopsy of the soft palate mass was revealed as NK/T cell lymphoma and was staged as Stage1b after computed tomographic imaging revealed a local tumour invasion without sign of nodal involvement and no metastasis. The patient eventually started with the SMILE Protocol and responded well up to the date. The ulcer healed but the fistula persisted. Primary closure was planned by the oromaxillofacial surgery team after completion of chemotherapy.